Low Cost Microcontroller Based Automatic Billing System with Protective Shielding from RF Waves - Suganthi Evangeline (International Journal of Reconfigurable and Embedded Systems (IJRES), 2016)
Shopping Mall is a complex of shops representing various merchandisers that enables the customers to buy all their needed things. As it is easier for people to come and buy all their things in a common place, shopping malls are crowded. As people are coming in large numbers to buy the groceries and house hold products for the full month, the billing counters are flooded with people. In order to avoid such large queues at the billing counter, we are coming up with Smart Cart using newly evolved RFID Technology. In our proposed method, the bill is automatically generated in the trolley as the customer purchases the product.